2011
DOI: 10.2337/dc10-2386
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Physical Activity and the Subsequent Risk of Incident Dysglycemia

Abstract: OBJECTIVETo investigate pedometer-measured physical activity (PA) in 2000 and change in PA over 5 years with subsequent risk of dysglycemia by 2005.RESEARCH DESIGN AND METHODSThis prospective cohort study in Tasmania, Australia, analyzed 458 adults with normal glucose tolerance and a mean (SD) age of 49.7 (12.1) years in 2000. Variables assessed in 2000 and 2005 included PA, by pedometer and questionnaire, nutrient intake, and other lifestyle factors. Incident dysglycemia was defined as the development of impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 24 publications
2
42
1
1
Order By: Relevance
“…Some researchers have suggested only a small increase in daily steps is enough to improve outcomes like body weight (Hill, 2005). In support of this notion, recent observational data suggests increasing daily steps by as little as 1,000-2,500 steps/day from a baseline similar to that reported in the current study might be enough to prevent dysglycemia and other cardiometabolic related outcomes (Dwyer et al, 2011;Ponsonby et al, 2011). However, other research has suggested glycemia is not meaningfully influenced by previous levels of physical activity among a large sample of individuals at increased risk for diabetes with an estimated steps/day count of approximately 6,500 (Yates et al, 2015).…”
Section: Discussionsupporting
confidence: 65%
“…Some researchers have suggested only a small increase in daily steps is enough to improve outcomes like body weight (Hill, 2005). In support of this notion, recent observational data suggests increasing daily steps by as little as 1,000-2,500 steps/day from a baseline similar to that reported in the current study might be enough to prevent dysglycemia and other cardiometabolic related outcomes (Dwyer et al, 2011;Ponsonby et al, 2011). However, other research has suggested glycemia is not meaningfully influenced by previous levels of physical activity among a large sample of individuals at increased risk for diabetes with an estimated steps/day count of approximately 6,500 (Yates et al, 2015).…”
Section: Discussionsupporting
confidence: 65%
“…The Tasped cohort was developed by pooling three pre-existing cohort studies based on Tasmanian adults–the Australian Diabetes Obesity and Lifestyle (AUSDIAB) study, [ 21 , 22 ] the Tasmanian Older Adult Cohort (TASOAC) study [ 23 ] and the Tasmanian Study of Cognition and Gait (TASCOG) study. [ 24 ] The Tasped cohort participants were linked to the National Death Index, compiled by the Australian Institute of Health and Welfare for all Australian deaths, to determine mortality up to June 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The summary PA measure for each period was the average daily number of steps over two consecutive days where at least one was a weekday. We have previously established this measure of daily steps is inversely and prospectively associated with hypertension (AOR 0.87 (95% CI 0.77–0.97)) [ 22 ] and insulin sensitivity and adiposity in free-living adults. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect a difference in daily steps, both groups were calculated to need 25 participants when using a one‐sided test with a power of 80% and an alpha level of 0·05. We decided to also conservatively include 25 participants in the DM group as reported daily steps in patients with diabetes were 10 500 ± 4000 . Thus, 75 participants were required.…”
Section: Methodsmentioning
confidence: 99%